Description of Thorichthys panchovillai sp. n., a new species of cichlid (Actinopterygii: Cichlidae) from the River Coatzacoalcos Basin, Mexico - Del Moral-Flores, Luis Fernando (2017)
Thorichthys panchovillai, new species, is described, from distinctive of the tributaries of the River Coatzacoalcos basin, Mexico. The new species is diagnosed by a set of characters: dorsal fin rays XVI, 8 – 9; anal fin rays VII, 6 – 7; pectoral fin rays, I, 11 – 12; total gill-rakers on the first branchial cleft 11 – 12; subopercular stain present although weakly intensified, it exposes a notable sexual dimorphism that distinguishes it from others: the female possess a black blotch between the fifth and sixth dorsal spine.